The Role of Bhabinkamtibmas through Internal Counseling in the Prevention of Fraud Crimes in the Jurisdiction of Jombang Police - Lase, Abdullah Roni (Indonesian Journal of Police Studies, 2024)
Today the percentage of crime is increasing compared to security and order. One of the crimes that many commit is fraud. Jombang Regency is one of the regions in East Java Province that has experienced an increase in fraud cases. The purpose of this study is to explain the implementation of activities, influencing factors, and the role of Bhabinkamtibnas in fostering counseling on fraud prevention in the jurisdiction of the Jombang Police Station. This study uses the concept of bhabinkamtibmas, the concept of kamtibmas counseling coaching, and the concept of crime prevention. For the first problem formulation using social communication theory with the components of who (who), say what (say what), which channel (in what channel), to whom (to whom), and what effect (what effect). The second problem formulation uses SWOT analysis theory with a composition, namely strengths, weaknesses, opportunities, and threats. For the formulation of the third problem using competency theory with elements of competence, namely knowledge, abilities, and attitudes. This research uses a qualitative approach with a type of analytical descriptive research. Data collection techniques are carried out by observation, interviews, and document studies. The results showed that the implementation of counseling in the prevention of fraud in Jombang has been well implemented by Bhabinkamtibmas, although there are still several inhibiting factors such as areas that are difficult to access, human resources that have not met the DSP, and lack of access to technology and information. Bhabinkamtibmas plays a very important role in conveying messages or materials to the community in fostering counseling on fraud prevention.